2017
DOI: 10.1111/soin.12211
|View full text |Cite
|
Sign up to set email alerts
|

Multilingualism and European Identification

Abstract: The literature on ethnicity and nationalism notes the centrality of language in group formation. Developments connected to globalization have simultaneously propitiated learning more than one language and the emergence of post‐national and pan‐ethnic identifications. This article brings the literature on ethnicity and nationalism to bear on the analysis of these changes to assess the causal relationship between multilingualism (ML) and European identification (EI). Sociology and social psychology provide solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 60 publications
1
13
0
2
Order By: Relevance
“…In relation to European identification, a few empirical studies have examined and found that identification with Europe is stronger among people who are able to speak more languages (e.g., Fuss et al, 2004;Medrano, 2018). For example, using data from the Eurobarometer, Medrano (2018) found that greater number of languages known predicts greater European identification even when controlling for demographic variables such as age and education.…”
Section: Language and Social Identitymentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to European identification, a few empirical studies have examined and found that identification with Europe is stronger among people who are able to speak more languages (e.g., Fuss et al, 2004;Medrano, 2018). For example, using data from the Eurobarometer, Medrano (2018) found that greater number of languages known predicts greater European identification even when controlling for demographic variables such as age and education.…”
Section: Language and Social Identitymentioning
confidence: 99%
“…In relation to European identification, a few empirical studies have examined and found that identification with Europe is stronger among people who are able to speak more languages (e.g., Fuss et al, 2004;Medrano, 2018). For example, using data from the Eurobarometer, Medrano (2018) found that greater number of languages known predicts greater European identification even when controlling for demographic variables such as age and education. However, and as will be detailed further, these studies (1) focus on self-reported language ability or number of languages known rather than regular foreign language usage, (2) do not simultaneously consider national identification, and (3) do not test the psychological mechanisms that might explain the relationships between multilingualism and European and national identification.…”
Section: Language and Social Identitymentioning
confidence: 99%
See 3 more Smart Citations